Developing Student Emotional Intelligence by Involving the Active Role of Teacher - Jolanda Dessye Parinussa; Taryana Taryana; Anisa Aurum Ningtyas; Reza Saeful Rachman; Hendy Tannady (Departement of Mathematics Education, 2023)
This research is specifically aimed at elementary school teachers who have a big role in the child's education process. Perfect education is of course visualized by balancing all abilities and potentials within the child. Researchers want educators to be able to consider taking a bigger role in instilling students' emotional intelligence. In this study, the method used is mixed methods, which means combining two forms of research that have existed before, namely quantitative and qualitative research. Qualitative research is research that is descriptive in nature and uses a lot of analysis with an inductive approach. The qualitative approach emphasizes meaning, definition of certain conditions, and examines matters relating to everyday life. The conclusion from this study is that teachers should be able to provide advice and provide examples of exemplary attitudes for students to emulate, such as by providing examples in daily actions. Give a simple parable but can be understood by students. By giving parables such as profit and loss, to teach students that what we do can bring good (profit) or actually bring bad (loss) and also gives other parables such as cause and effect, so that students understand that what they do will have an impact on them.